English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

(2a -3)² = (2a)² - 2(2a3) + 3² = 4a² - 12a + 9
<>

2006-12-10 16:08:12 · answer #1 · answered by aeiou 7 · 1 0

(2a -3)(2a -3) =
4a^2 - 6a - 6a + 9 =
4a^2 -12a + 9

Note that -12 = 2(2)(-3)

The general case is
(a + b)(a + b) =
a^2 + ab + ab + b^2 =
a^2 + 2ab + b^2,
so for binomial squares, the middle term is always 2(1st term)(last term)

2006-12-10 16:16:56 · answer #2 · answered by Helmut 7 · 1 0

Just multiply it out using FOIL.


Doug

2006-12-10 16:10:36 · answer #3 · answered by doug_donaghue 7 · 1 0

(a - b) squared is
a squared - 2ab + b squared. Memorize that one.

2006-12-10 16:04:40 · answer #4 · answered by alwaysmoose 7 · 1 0

fedest.com, questions and answers